THE INFLUENCE OF PICTURE COLORING ON FINE MOTOR DEVELOPMENT IN CHILDREN AGED 4-5 YEARS - Nining Fitrianingsih; Noor Siti Noviani Indah Sari (Universitas Pakuan, 2019)
According to the World Health Organization (WHO) reports that 2-25% of preschool age children suffer from minor brain dysfunction, including impaired fine motor development, in Indonesia around 16% of children experience impaired fine motor development. Fine motor development involves certain body parts performed by small muscles. How to stimulate fine motor skills in children has a very large function, namely to increase the movement of fine activities such as writing, drawing, and typing. The impact that will occur if the child has a disruption in fine motor development that can cause cerebral palcy. To determine the effect of coloring pictures on fine motor development in children aged 4-5 years. This type of research is pre-experimental and conducted in Al-Munawar Kindergarten, Nanggung District with respondents, namely children aged 4-5 years using Total Sampling. The instrument used was an observation sheet. Knowing univariate analysis before given coloring treatment 50% of children in the category of undeveloped and after being given coloring treatment 50% of children in the development category as expected. Bivariate analysis using the normality test using Shapiro Wilk with the results of 0,000 0.05 means that the data is not normally distributed, after that to test the hypothesis using Willcoxon with a P value of 0,000 0.05, it means that Ha is accepted. Knowing fine motor development of the respondents 50% of respondents fall into the category of undeveloped with a mean value of 1.87 and a standard deviation of 0.937. Knowing fine motor development of 50% of respondents included in the category of developing according to expectations with a mean value of 2.90 and a standard deviation of 0.712. The Influence of Coloring Pictures Against Fine Motoric Development in Children Aged 4-5 Years at Al-Munawar Kindergarten, Nanggung District, Bogor Regency.